Anticonvulsant activity of p-chlorophenyl substituted arylsemicarbazones - The role of primary terminal amino group - Pandeya S.N.; Mishra V.; Ponnilavarasan I.; Stables J.P. (My University, 2025)
A series of p-chlorophenyl substituted arylsemicarbazones were synthesized and evaluated for anticonvulsant activity. Most of the compounds provided significant protection against maximal electroshock-induced seizures (MES) at 100 mg/kg after 0.5 h and at 300 mg/kg after 4 h in both MES and pentetrazole-induced (PTZ) seizures. In the strychnine-induced seizures (scSTY), the majority of the compounds showed protection at 30 mg/kg. The compound 2 was active in both MES and PTZ tests. The study has shown that the terminal primary amino group is not necessary for anticonvulsant activity.